Interview Sequences and the Formation of Subjective Assessments - Jonas Radbruch; Amelie Schiprowski (Institute of Labor Economics (IZA), 2021)
Interviewing is a decisive stage of most processes that match candidates to firms or organizations. This paper studies how and why the interview assessment of a candidate depends on the other candidates seen by the same evaluator. We leverage novel administrative data covering about 29,000 one-to-one interviews from a study grant admission process where candidates are quasi-randomly assigned to evaluators and time slots. We find that a candidate's assessment decreases in the quality of the other candidates seen by the same evaluator, and most strikingly in the quality of the previous candidate. This effect is strongest when candidates are similar in terms of their observable characteristics. The reduced-form patterns and the results of a structural estimation suggest that evaluators exhibit a contrast effect which is caused by the interplay between the associative recall of prior candidates and the attention to salient quality differences.
Keywords: D91; M51; 330; interviewing; associative recall; contrast effect